Investigations of the Rural Sanctuary at the Settlement of Artyushchenko-1 (Bugazskoe) on the Taman Peninsula in 2015–2018 - Vinogradov, Yuriy A. (Hyperboreus, 2019)
A survey of the excavations at the settlement of Artyushchenko-1 (Bugazkoe) conducted by the Bosporan expedition of the Institute for the History of Material Culture, RAS in 2015-2018.